Makna kebersyukuran mahasiswa part-time di perpustakaan perguruan tinggi terhadap kesejahteraan psikologis - Al Husna, Hana Isnaini; Utami, Marni; Susanti, Eska Agustin Putri (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2025)
Background of the Study: This study explores how part-time university library workers interpret gratitude while balancing their dual roles as students and employees. Libraries are not only hubs for information and academic services but also provide a work environment for students to gain work experience. Objectives:  This research aimed to understand the meaning of gratitude among part-time student workers in university libraries and how gratitude contributes to their psychological well-being while fulfilling academic and work responsibilities. Method: This study used a qualitative phenomenological approach. Data were collected through in-depth interviews with students who had completed their coursework and were in the process of writing their final projects. The collected data were analyzed using Ryff’s theory of psychological well-being and Emmons’ concept of gratitude. Finding: The findings reveal that gratitude is not merely a reaction to positive experiences but a meaningful attitude that supports psychological well-being. Eight key factors were found to foster gratitude among part-time student workers: (1) job opportunities aligned with personal interests, (2) social support, (3) skill development, (4) financial stability, (5) time management ability, (6) appreciation for work, (7) independence and responsibility, and (8) acceptance of challenges. These factors correspond to Ryff’s six dimensions of psychological well-being and reinforce Emmons’ idea of gratitude as a psychological strength. Overall, part-time work experience helps students develop resilience, adaptability, and a sense of purpose. Conclusion: From the results of this study, it can be concluded that gratitude functions not only as an emotional response but also as a positive mindset that enables part-time student workers to face the pressures of dual roles with composure and emotional balance. Further quantitative research and studies across various types of part-time work are needed to strengthen these findings.